2021
DOI: 10.1016/j.jbc.2021.100647
|View full text |Cite
|
Sign up to set email alerts
|

Major advances in targeted protein degradation: PROTACs, LYTACs, and MADTACs

Abstract: Of late, targeted protein degradation (TPD) has surfaced as a novel and innovative chemical tool and therapeutic modality. By co-opting protein degradation pathways, TPD facilitates complete removal of the protein molecules from within or outside the cell. While the pioneering Proteolysis-Targeting Chimera (PROTAC) technology and molecular glues hijack the ubiquitin-proteasome system, newer modalities co-opt autophagy or the endo-lysosomal pathway. Using this mechanism, TPD is posited to largely expand the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 183 publications
(230 reference statements)
0
131
0
2
Order By: Relevance
“…These classes include autophagy-targeting chimeras (AUTACs), autophagosome-tethering compounds (ATTECs), lysosome-targeting chimeras (LYTACs) and antibody-based PROTACs (AbTACs). Collectively, AUTACs and ATTECs have also been categorized as macroautophagy degradation-targeting chimeras (MADTACs) 248 . Like PROTACs, AUTECs and ATTECs focus on intracellular triggering of TPD, while LYTACs and AbTACs trigger intercellular TPD via an extracellular process.…”
Section: Outlook For the Next 20 Years Of Tpdmentioning
confidence: 99%
“…These classes include autophagy-targeting chimeras (AUTACs), autophagosome-tethering compounds (ATTECs), lysosome-targeting chimeras (LYTACs) and antibody-based PROTACs (AbTACs). Collectively, AUTACs and ATTECs have also been categorized as macroautophagy degradation-targeting chimeras (MADTACs) 248 . Like PROTACs, AUTECs and ATTECs focus on intracellular triggering of TPD, while LYTACs and AbTACs trigger intercellular TPD via an extracellular process.…”
Section: Outlook For the Next 20 Years Of Tpdmentioning
confidence: 99%
“…Further advancement in computational analysis and structure-based optimization methods will likely result in better PROTAC linker design. A more extensive overview of the different linker classes, effects on the multiple aspects of PROTACs properties, and emerging design principles can be found here [ 380 , 381 ].…”
Section: Targeted Protein Degradationmentioning
confidence: 99%
“…At present, several challenges remain regarding the development of PROTAC molecules, namely, the rational design of bifunctional molecules and the expansion of the use of various types of E3 ligases other than the currently used ligases (VHL, CRBN, cIAPs, and MDM2) [105]. Moreover, the precise mechanism of action of the degradation machinery in several techniques, including AUTAC, remains unclear [106,107]. A recent report demonstrated that PROTAC-based polyubiquitination could be facilitated by the thyroid hormone receptor-interacting protein 12 (TRIP12), rather than the hijacking of the enzyme by an E3 ligase binder, thus highlighting a role for TRIP12 as an accelerator of PROTAC-directed degradation [108].…”
Section: Discussionmentioning
confidence: 99%